Analisis Indeks Glikemik dan Sifat Fisik Beras Analog Sebagai Alternatif Pangan Fungsional pada Penderita Diabetes Mellitus: Analysis of Glycemic Index and Physical Properties of Analog Rice as an Alternative Functional Food for Individuals with Diabetes Mellitus - Vivi Meiliza Majid; Arif Sabta Aji; Satrijo Saloko; Veriani Aprilia; Dina Seftina; Ika Wahyuningsih (Universitas Airlangga, 2025)
Background: Food diversification is essential for managing Diabetes Mellitus (DM). Analog rice made from sorghum, modified cassava flour (MOCAF), moringa leaves, and glucomannan may serve as a functional food. Objectives: This study aims to evaluate the glycemic index (GI) and physical properties of analog rice as a potential functional food for individuals with DM. Methods: This experimental study employed a Completely Randomized Design (CRD) with two replications, involving six treatment groups with varying moringa leaf flour substitutions: P1 (0%), P2 (2%), P3 (4%), P4 (6%), P5 (8%), and P6 (10%), totaling twelve samples. Thirty male Wistar rats (Rattus norvegicus) were used for GI determination, calculated from the area under the curve (AUC) of postprandial blood glucose responses. Physical properties assessed were cooking time, bulk density, rehydration capacity, stickiness, expansion volume, and color. Results: The GI of analog rice ranged from 8.92 to 32.67 and differed significantly among treatments (p-value≤0.001). Moringa leaf substitution significantly affected rehydration capacity (p-value≤0.001), stickiness (p-value≤0.001), and color parameters—greenness (p-value=0.002), yellowness (p-value=0.004), and lightness (p-value=0.390). Meanwhile, bulk density (p-value=0.198) and expansion volume (p-value=0.153) were not significantly affected. Conclusions: Treatment 2 (2% moringa leaf flour) produces the most favorable analog rice, with low GI, low bulk density, optimal stickiness, bright green color, and 15-minute cooking time. This formulation shows potential as a functional food alternative for individuals with DM.